Osteoid Osteoma Ablation in the Hand Using CT-guided Radiofrequency: Methodology. Issue 4 (December 2021) - Zinger, Gershon; Adler, Shana; Applbaum, Yaakov; Peyser, Amos
Abstract : Osteoid osteoma (OO) is a painful benign vascular lesion rarely found in the hand. Treatment includes resection, usually done with a standard open approach. Radiofrequency uses radio waves to transmit energy to local tissue to ablate the lesion with thermal necrosis. It is often used for OO in the proximal extremities and spine but rarely in the hand. We present a case here of OO ablation using radiofrequency in the fourth metacarpal head. The procedure was minimally invasive using a 3 mm dorsal incision and computed tomography guidance. We illustrate the technique used here that was both effective and avoided injury to nearby neurovascular structures.